Pengembangan media pembelajaran operasi aljabar berbasis articulate storyline berbantuan quizwhizzer untuk mendukung pemahaman konsep - Umi Latifatul Karima; Ana Rahmawati; Dian Novita Rohmatin (IKIP Siliwangi, 2024)
The purpose of this research are to describe the development process and result of algebra-based learning media by articulate storyline with help quizwhizzer website of valid, practical, and effective to support the student’s concept of understanding in algebra. This research model is ADDIE type, which has five steps, they are : analyse, design, development, implementation, and evaluation. Algebra-based learning media by articulate storyline with help quizwhizzer websitewas tested by two examinations, which are limited examination and direct examination to studenst of MTs Al-Mahrusiyah Lirboyo Kediri. The research tools used were validated papers, student’s and teacher’s assessment response, and the sheets of concept understanding. Algebra-based learning media by articulate storyline with hrlp quizwhizzer website has reached the validity percentage of 79,6%. The practical result showed the number 83%, previewed from studen’s assessment response. Therefore, it is valid to state that it has fulfilled the practical criteria. The effectiveness result showed 72% previewed from the result of student’s concept of understanding test. In addition to that, it has fulfilled the criteria effectively.